Szkolenia w organizacji i ich wpływ na rozwój pracowników - analiza procesu, technik i narzędzi - Tobiasz, Agnieszka (My University, 2012)
W niniejszej pracy omówione zostały zagadnienia związane z zarządzaniem zasobami ludzkimi oraz szczegółowo proces szkoleniowy w organizacji. Praca została oparta o literaturę przedmiotu. Celem pracy było zaprezentowanie całego procesu w wybranej firmie oraz wpływ szkolenia na pracowników. Zastosowano metodę ankiety. Wykorzystano 50 pozycji bibliograficznych.

This thisis discusses issues related to the management of human resources, and describes in detail the process of training in the organization. The thisis was based on the literature of the subject. Purpose of the thisis was to explain the entire process in the selected company’s, and the impact of training on the staff. I use the method of survey. And over 50 heading bibliographica sourses.
Training in the organization and it’s impact on the development of employees - analysis of the process, techniques and tools
Keywords: zasoby ludzkie; szkolenia; rozwój; pracownicy; ankieta; human resources; training; development; employees; questionnaire